On rank one perturbation of continuous spectrum which generates given finite point spectrum - Diaba, F.; Cheremnikh, E. V. (Methods of Functional Analysis and Topology, 2008)
The perturbations of Nevanlinna type functions which preserve the set of zeros of this function or add to this set new points are discussed.